Bibliometric Analysis of Triggers on Environmental Stress Among Medical and Health Sciences Students at the University - Kurniawan, Wawan; Pranata, Satriya; Vranada, Aric; Agustini, Aat; Irham, Lalu Muhammad (Scripta Medica, 2024)
Continuing to improve services to students while studying on campus, lecturers and all elements at the university need information about triggers of environmental stress among medical and health sciences students. Thus, the purpose of this study was to explore triggers of environmental stress among medical and health sciences students in the university through bibliometric analysis by analysing the network visualisation, overlay visualisation and density visualisation on the topic. Bibliometrics analysis was used in assessing related topics. The data sources are based on online searches via https://app.dimensions.ai/. Data was collected on 3 December 2023. The literature followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart. Data were analysed using VOSviewer and further analysed and reviewed by co-occurrence and co-authors. Four major themes of environmental stress were found in this study: 1) The internal situation in the university; 2) External situations outside of the university; 3) Comfort situation during the study; 4) Academic process. Environmental stress factors related to internal situation in the academic situation were academic stress, air pollution, anxiety in the academic process, COVID-19, depression, fear, medical student, nursing student, physical activity, school regulation, smoking and uncertainty of study. From the visualisation and density visualisation, it can be seen that the academic process related to the duration of study was a trending theme discussed in several papers related to triggers of environmental stress among students in the university. All elements of the university especially policy makers should pay attention to this problem to reduce the risk of stress while students are studying.